Reactive curing agents
By using a specific club as a reactive curing agent, the problem of insufficient solubility and insufficient heat resistance in existing technology in existing technology, and realized the heat resistance of high -soluble and thermal solution compositions in MEK promote.
Patent Information
- Application Number
- CN202380043187.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-14
- Filing Date
- 2023-06-07
- Publication Date
- 2025-01-21
AI Technical Summary
The existing reactive curing agents have insufficient solubility in methyl ethyl ketone (MEK) and cannot effectively improve the heat resistance of the thermosetting resin composition.
The co -concentrations containing aromatic ethylene -based monomers, unsaturated acid anhydride monomers, and Malaysanide monomers are used as reactive curing agents to ensure that the average molecular weight of the symbol is more than 10,000 and lower than 90,000. The Malayanamide is a single unit with a mass of more than 3.0 % or more and less than 49.0 % in the consequences.
It significantly improves the solubility of the reactive curing agent in the MEK, and improves the heat resistance of the thermosetry resin composition, so that it is suitable for the use of heat resistance for copper foil layer pressure plates.
Smart Images

Figure BDA0005155436630000241 
Figure BDA0005155436630000251 
Figure BDA0005155436630000261
Abstract
Description
Technical Field
[0001] The invention relates to a reactive curing agent. Background Art
[0002] Copper clad laminate (CCL) is known as a printed circuit board for electrically connecting / insulating electronic parts constituting a circuit and mechanically arranging / fixing parts. CCL is obtained by impregnating glass fiber with a thermosetting resin composition containing an epoxy resin or a polyphenylene ether resin and a reactive curing agent to obtain a semi-cured resin sheet, i.e., a prepreg, sandwiching both sides of the prepreg with copper foil, overlapping a plurality of sheets in this state, and performing heat compression bonding.
[0003] As a reactive curing agent, styrene-maleic anhydride copolymer (SMA) is often used because of its low dielectric loss. In addition, it is also known that styrene (St)-maleic anhydride (MAH)-N-phenylmaleimide (NPMI) copolymer can be used as a reactive curing agent (Patent Documents 1 to 4).
[0004] [Prior art documents]
[0005] [Patent Document]
[0006] [Patent Document 1] Japanese Patent Publication No. 2022-508173
[0007] [Patent Document 2] Japanese Patent Application Laid-Open No. 2020-169276
[0008] [Patent Document 3] Japanese Patent 5474561
[0009] [Patent Document 4] Japanese Patent 4807434 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] The present invention aims to provide a reactive curing agent having improved solubility in methyl ethyl ketone (MEK) and capable of improving the heat resistance of a thermosetting resin composition.
[0012] Solutions for solving problems
[0013] The present inventors have conducted research and found that the solubility in MEK and the heat resistance of the thermosetting resin composition can be improved by using the following reactive curing agent: the reactive curing agent comprises a copolymer comprising an aromatic vinyl monomer unit, an unsaturated acid anhydride monomer unit, and a maleimide monomer unit, and the weight average molecular weight of the copolymer is 10,000 or more and less than 90,000, and when the total of the monomer units contained in the copolymer is set to 100% by mass, the copolymer comprises 3.0% by mass or more and less than 49.0% by mass of the maleimide monomer unit.
[0014] That is, the present invention relates to the following contents:
[0015] [1] a reactive curing agent,
[0016] It comprises a copolymer containing an aromatic vinyl monomer unit, an unsaturated acid anhydride monomer unit, and a maleimide monomer unit, and
[0017] The weight average molecular weight of the copolymer is greater than or equal to 10,000 and less than or equal to 90,000.
[0018] The copolymer contains 3.0% by mass or more and less than 49.0% by mass of the maleimide-based monomer unit, when the total of the monomer units contained in the copolymer is 100% by mass.
[0019] [2] The reactive curing agent according to [1], wherein
[0020] When the total amount of the monomer units contained in the copolymer is 100% by mass, the copolymer contains 3.0 to 30.0% by mass of the maleimide-based monomer units.
[0021] [3] The reactive curing agent according to [2], wherein
[0022] When the total amount of the monomer units contained in the copolymer is 100% by mass, the copolymer includes:
[0023] 45.0 to 96.9% by mass of the above aromatic vinyl monomer units,
[0024] 0.1 to 25% by mass of the above unsaturated acid anhydride monomer units, and
[0025] 0.0 to 20.0% by mass of other monomer units.
[0026] [4] The reactive curing agent according to any one of [1] to [3], wherein
[0027] The number of the unsaturated acid anhydride monomer units contained in each molecular chain of the copolymer is 2 to 25.
[0028] [5] The reactive curing agent according to any one of [1] to [4], wherein
[0029] The glass transition temperature of the copolymer is 125-200°C.
[0030] [6] The reactive curing agent according to any one of [1] to [5], wherein
[0031] The weight average molecular weight of the copolymer is 15,000 to 80,000.
[0032] [7] The reactive curing agent according to any one of [1] to [5], wherein
[0033] The weight average molecular weight of the copolymer is 20,000 to 70,000.
[0034] Effects of the Invention
[0035] If the reactive curing agent of the present invention is used, the solubility in MEK is improved. In addition, the heat resistance of the thermosetting resin composition can be improved. Therefore, it is suitable for use in applications requiring heat resistance such as copper-clad laminates. DETAILED DESCRIPTION
[0036] <Explanation of Terms>
[0037] In the specification of this case, the description "A to B" means that A is greater than and B is less than.
[0038] Hereinafter, the embodiments of the present invention will be described in detail. The present invention is not limited thereto, and various changes can be made within the scope of the present invention. Various characteristic matters shown in the embodiments shown below can be combined with each other. In addition, the invention is established independently of each characteristic matter.
[0039] <Copolymer contained in reactive curing agent>
[0040] The reactive curing agent of the present embodiment includes a copolymer containing an aromatic vinyl monomer unit, an unsaturated acid anhydride monomer unit, and a maleimide monomer unit. The monomer units contained in the copolymer will be described below.
[0041] <Aromatic vinyl monomer unit>
[0042] As the source of the aromatic vinyl monomer units contained in the copolymer of the present embodiment, i.e., aromatic vinyl monomers, for example, styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, ethylstyrene, p-tert-butylstyrene, α-methylstyrene, α-methyl-p-methylstyrene, etc. Among them, styrene is preferred from the viewpoint of the solubility of the copolymer in MEK. The aromatic vinyl monomers can be used alone or in combination of two or more.
[0043] When the total of the monomer units contained in the copolymer is set to 100% by mass, the copolymer of the present embodiment preferably contains 45.0 to 96.9% by mass of aromatic vinyl monomer units, more preferably 45.0 to 89.9% by mass of aromatic vinyl monomer units, further preferably 55.0 to 85.0% by mass of aromatic vinyl monomer units, and particularly preferably 60.0 to 80.0% by mass of aromatic vinyl monomer units. Specifically, for example, preferably 45.0, 50.0, 55.0, 60.0, 65.0, 70.0, 74.0, 76.0, 78.0, 80.0, 82.0, 84.0, 85.0, 86.0, 88.0, 89.9, or 96.9% by mass, and may be in the range between any two of the numerical values exemplified herein. If the content of the aromatic vinyl monomer unit is 45.0% by mass or more, the solubility of the copolymer in MEK is improved, and if it is 96.9% by mass or less, the copolymer can contain more maleimide monomer units that can help improve the heat resistance, so the heat resistance of the thermosetting resin composition prepared with the copolymer is improved. The content of the aromatic vinyl monomer unit is determined by 13 The value measured by C-NMR (Carbon-Nuclear Magnetic Resonance).
[0044] When an aromatic vinyl monomer unit is used in combination, the content of the aromatic vinyl monomer unit means the total amount of the aromatic vinyl monomer units used in combination.
[0045] <Unsaturated acid anhydride monomer unit>
[0046] As the source of the unsaturated anhydride monomer units contained in the copolymer of the present embodiment, that is, the unsaturated anhydride monomer, for example, there are maleic anhydride, itaconic anhydride, citraconic anhydride, aconitic anhydride, etc. Among them, maleic anhydride is preferred from the viewpoint of imparting curability to the thermosetting resin composition formulated with the copolymer. The unsaturated anhydride monomer may be used alone or in combination of two or more.
[0047] When the total of the monomer units contained in the copolymer is set to 100% by mass, the copolymer of the present embodiment preferably contains 0.1 to 25% by mass of unsaturated anhydride monomer units, more preferably contains 0.1 to 8.0% by mass of unsaturated anhydride monomer units, further preferably contains 0.1 to 6.0% by mass of unsaturated anhydride monomer units, and particularly preferably contains 0.1 to 4.0% by mass of unsaturated anhydride monomer units. Specifically, for example, preferably 0.1, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 5.0, 6.0, 7.0, 8.0, 10, 15, 20 or 25% by mass, or in the range of any two of the numerical values exemplified herein. If the content of the unsaturated anhydride monomer unit is more than 0.1% by mass, the curability of the thermosetting resin composition with the copolymer is improved, and if it is less than 25% by mass, the thermal stability of the copolymer or the hygroscopic resistance or thermal stability of the thermosetting resin composition with the copolymer is improved. The content of unsaturated anhydride monomer units is determined by 13 The values were measured by C-NMR.
[0048] In addition, when an unsaturated acid anhydride monomer unit is used in combination, the content of the unsaturated acid anhydride monomer unit means the total amount of the unsaturated acid anhydride monomer units used in combination.
[0049] <Maleimide Monomer Unit>
[0050] As the source of the maleimide monomer unit contained in the copolymer of the present embodiment, that is, maleimide monomer, for example, there are N-alkyl maleimides such as N-methyl maleimide, N-butyl maleimide, N-cyclohexyl maleimide, and N-phenyl maleimide, N-chlorophenyl maleimide, N-methylphenyl maleimide, N-methoxyphenyl maleimide, N-tribromophenyl maleimide, etc. N-aryl maleimide. From the viewpoint of the thermal stability of the copolymer, preferably N-aryl maleimide, more preferably N-phenyl maleimide. Maleimide monomer can be used alone, and two or more kinds can also be used in combination.
[0051] In order to make the copolymer contain maleimide monomer units, for example, a raw material containing unsaturated acid anhydride monomer units is copolymerized with other monomers to obtain a copolymer, and the copolymer is imidized with ammonia or a primary amine. Alternatively, a raw material containing maleimide monomers can be copolymerized with other monomers.
[0052] When the total of the monomer units contained in the copolymer is set to 100% by mass, the copolymer of the present embodiment contains 3.0% by mass or more and less than 49.0% by mass of maleimide monomer units, preferably 3.0 to 30.0% by mass of maleimide monomer units, more preferably 14.0 to 28.0% by mass of maleimide monomer units, and further preferably 18.0 to 26.0% by mass of maleimide monomer units. Specifically, for example, preferably 3.0, 5.0, 8.0, 10.0, 12.5, 15.0, 17.5, 20.0, 22.5, 25.0, 27.5, 30.0, 35.0, 40.0, 45.0, 48.0, or 48.9% by mass, and may also be in the range between any two of the numerical values exemplified herein. If the content of the maleimide monomer unit is 3.0 mass % or more, the heat resistance of the thermosetting resin composition prepared with the copolymer is improved, and if it is less than 49.0 mass %, the solubility of the copolymer in MEK is improved. The content of the maleimide monomer unit is determined by 13 The values were measured by C-NMR.
[0053] In addition, when the maleimide-based monomer units are used in combination, the content of the maleimide-based monomer units means the total amount of the maleimide-based monomer units used in combination.
[0054] <Other monomer units>
[0055] The copolymer of the present embodiment may also use copolymerizable monomers other than aromatic vinyl monomers, unsaturated acid anhydride monomers, and maleimide monomers as other monomers, and copolymerize within the range that does not hinder the effect of the present invention. As other monomers that can be copolymerized with the copolymer of this embodiment, there can be cited: cyanide vinyl monomers, acrylate monomers, methacrylate monomers, vinyl carboxylic acid monomers, acrylamide, and methacrylamide. Among them, from the viewpoint of affinity with epoxy resin, cyanide vinyl monomers and methacrylate monomers are preferred.
[0056] Examples of the vinyl cyanide monomer include acrylonitrile, methacrylonitrile, ethacrylonitrile, and butylenedinitrile.
[0057] Examples of the acrylic acid ester monomer include methyl acrylate, ethyl acrylate, and butyl acrylate.
[0058] Examples of the methacrylate monomer include methyl methacrylate and ethyl methacrylate.
[0059] Examples of the vinyl carboxylic acid monomer include acrylic acid and methacrylic acid.
[0060] Other monomers that can be copolymerized to form a copolymer may be used alone or in combination of two or more.
[0061] Such other copolymerizable monomers can be copolymerized within the range that does not hinder the effect of the present invention, but from the viewpoint of the balance between affinity with epoxy resin and solubility in MEK, when the total of the monomer units contained in the copolymer is set to 100% by mass, it is preferred to contain 0.0 to 20.0% by mass of other monomer units, more preferably 0.1 to 10.0% by mass of other monomer units, and further preferably 0.5 to 5.0% by mass of other monomer units. Specifically, for example, it is preferably 0.0, 0.5, 1.0, 2.0, 5.0, 10.0, 15.0, or 20.0% by mass, and may also be within the range between any two of the numerical values exemplified here. When other monomer units are contained, the affinity with epoxy resin is improved, and if it is less than 20.0% by mass, the solubility in MEK is improved. The content of other monomer units is determined by 13 The values were measured by C-NMR.
[0062] When other monomer units are used in combination, the amount thereof refers to the total amount of other monomer units used in combination.
[0063] <Additives contained in reactive curing agent>
[0064] The reactive curing agent of the present embodiment may contain the additives described below within a range that does not inhibit the effects of the present invention.
[0065] After the polymerization of the copolymer contained in the reactive curing agent is completed, heat stabilizers such as hindered phenol compounds, lactone compounds, phosphorus compounds, sulfur compounds, hindered amine compounds, benzotriazole compounds, light stabilizers, lubricants, or plasticizers, colorants, antistatic agents, mineral oils and other additives can be added to the polymerization solution as needed. Relative to 100 parts by mass of all monomer units, the amount added is preferably less than 0.2 parts by mass. These additives can be used alone or in combination of two or more.
[0066] <Production of Copolymer>
[0067] The polymerization method of the copolymer contained in the reactive curing agent of the present embodiment includes, for example, solution polymerization, block polymerization, etc. From the viewpoint that the copolymer having a more uniform copolymer composition can be obtained by polymerizing by adding separately, solution polymerization is preferred. From the viewpoint that it is not easy to produce by-products and has few adverse effects, the solvent for solution polymerization is preferably non-polymerizable. For example, ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, acetophenone, tetrahydrofuran, ethers such as 1,4-dioxane, benzene, toluene, xylene, chlorobenzene, aromatic hydrocarbons, N,N-dimethylformamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, etc., are preferably methyl ethyl ketone and methyl isobutyl ketone from the ease of solvent removal during de-volatilization recovery of the copolymer. The polymerization process can be applied to any of continuous polymerization, batch (batch), and semi-batch.
[0068] The method for producing the copolymer of the present embodiment is not particularly limited, and it is preferably obtained by free radical polymerization, and the polymerization temperature is preferably within the range of 80 to 150°C. As a polymerization initiator, it is not particularly limited, and for example, known azo compounds such as azobisisobutyronitrile, azobiscyclohexanecarbonitrile, azodimethylpropionitrile, azodimethylbutyronitrile, or benzoyl peroxide, tert-butyl peroxybenzoate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-butylperoxyisopropylmonocarbonate, tert-butyl peroxy 2-ethylhexanoate, di-tert-butyl peroxide, diisopropylphenyl peroxide, 3,3-di(tert-butylperoxy)ethyl butyrate, etc., known organic peroxides, can be used, and one of them can be used or two or more can be used in combination. From the viewpoint of polymerization reaction speed or polymerization rate control, it is preferred to use an azo compound or organic peroxide with a 10-hour half-life of 70 to 120°C. The amount of the polymerization initiator used is not particularly limited, and is preferably 0.1 to 1.5% by mass, more preferably 0.1 to 1.0% by mass, relative to 100% by mass of all monomer units. If the amount of the polymerization initiator used is 0.1% by mass or more, sufficient polymerization rate can be obtained, so it is preferred. If the amount of the polymerization initiator used is 1.5% by mass or less, the polymerization rate can be suppressed, so it is easy to control the reaction and it is easy to obtain the target molecular weight.
[0069] The manufacture of the copolymer of the present embodiment can use a chain transfer agent. As the chain transfer agent used, it is not particularly limited, for example, there are n-octyl mercaptan, n-dodecyl mercaptan, tert-dodecyl mercaptan, α-methyl styrene dimer, ethyl thioglycolate, limonene, terpinene, etc. The amount of the chain transfer agent is not particularly limited, as long as it is within the range of the target molecular weight, relative to 100% by mass of all monomer units, preferably 0.01 to 2.0% by mass, and more preferably 0.1 to 1.5% by mass. If the amount of the chain transfer agent used is 0.01% to 1.2% by mass, the target molecular weight can be easily obtained.
[0070] As a method for introducing maleimide monomer units into the copolymer of the present embodiment, there are the following methods: a method of copolymerizing maleimide monomers, aromatic vinyl monomers and other monomers (direct method); or a method of pre-copolymerizing unsaturated anhydride monomers, aromatic vinyl monomers and other monomers, and then reacting the unsaturated anhydride groups with ammonia or primary amine to convert the unsaturated anhydride groups into maleimide monomer units (post-imidization method). The post-imidization method is more preferred because the amount of residual maleimide monomers in the copolymer is reduced.
[0071] The primary amines used in the post-imidization method include, for example, alkylamines such as methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, n-pentylamine, n-hexylamine, n-octylamine, cyclohexylamine, and decylamine, and aromatic amines such as chlorine or bromine substituted alkylamines, aniline, toluidine, and naphthylamine, among which aniline and cyclohexylamine are preferred. These primary amines can be used alone or in combination of two or more. The amount of primary amine added is not particularly limited, and is preferably 0.7 to 1.1 molar equivalents relative to the unsaturated anhydride group, and more preferably 0.85 to 1.05 molar equivalents. If it is 0.7 molar equivalents or more relative to the unsaturated anhydride monomer unit in the crude product raw material, the thermal stability of the copolymer is good, so it is preferred. In addition, if it is less than 1.1 molar equivalents, the amount of primary amine remaining in the copolymer is reduced, so it is preferred.
[0072] A catalyst may also be used when the maleimide monomer unit is introduced by the post-imidization method. The catalyst can improve the dehydration ring-closing reaction in the reaction of ammonia or primary amine with the unsaturated anhydride group, especially in the reaction of converting the unsaturated anhydride group into the maleimide group. The type of catalyst is not particularly limited, and for example, a tertiary amine can be used. As the tertiary amine, there is no particular limitation, and for example, trimethylamine, triethylamine, tripropylamine, tributylamine, N,N-dimethylaniline, N,N-diethylaniline, etc. can be cited. The amount of tertiary amine added is not particularly limited, and is preferably 0.01 molar equivalent or more relative to the unsaturated anhydride group. The temperature of the imidization reaction in the present invention is preferably 100 to 250°C, and more preferably 120 to 200°C. If the temperature of the imidization reaction is 100°C or more, the reaction rate is sufficiently fast, which is preferred in terms of productivity. If the temperature of the imidization reaction is 250°C or less, it is preferred because the reduction in physical properties caused by thermal degradation of the copolymer can be suppressed.
[0073] The method for removing volatile components such as the solvent used in solution polymerization or unreacted monomers from the solution after the solution polymerization of the copolymer or the solution after the post-imidization (devolatilization method) can be a known method. For example, a vacuum devolatilization tank with a heater or a devolatilization extruder with an exhaust port can be used. The molten copolymer after devolatilization can be transferred to the granulation step, extruded in a strand state from a porous die, and processed into granules by cold cutting, air heat cutting, or water heat cutting. For the obtained granules, the copolymer can be processed into a powder through a crushing step. By making the copolymer into a powder, it has the advantage of faster dissolution rate when formulated in a thermosetting resin composition. Furthermore, when the weight average molecular weight of the copolymer is reduced, it can also be processed into a powder by recovering the extruded copolymer and crushing it without going through the granulation step. There is no particular limitation as to the crushing method, and a known crushing technology can be used. Examples of the pulverizing apparatus that can be suitably used include a rotary blade pulverizer, a turbine pulverizer, a turbine disc pulverizer, a turbine cutter pulverizer, a jet pulverizer, an impact pulverizer, a hammer pulverizer, and a vibration pulverizer.
[0074] <Weight Average Molecular Weight (Mw) of Copolymer>
[0075] The weight average molecular weight (Mw) of the copolymer of the present embodiment is 10,000 or more and less than 90,000, preferably 15,000 to 80,000, more preferably 20,000 to 70,000, and further preferably 30,000 to 70,000. Specifically, for example, it is preferably 1, 2, 3, 4, 5, 6, 7, 8, or 89,000, and may also be in the range between any two of the numerical values exemplified herein. If the weight average molecular weight (Mw) of the copolymer is 10,000 or more, the amount of chain transfer agent used in the polymerization step of the copolymer is reduced, so that the amount of VOC (volatile organic compounds) contained in the obtained copolymer can be reduced. If it is less than 90,000, the solubility of the copolymer in MEK can be improved.
[0076] To control the weight average molecular weight (Mw) of the copolymer, in addition to adjusting the polymerization temperature, polymerization time, and the amount of polymerization initiator added, there are also methods such as adjusting the solvent concentration and the amount of chain transfer agent added.
[0077] The weight average molecular weight (Mw) of the copolymer is a value in terms of polystyrene measured by gel permeation chromatography (GPC), and can be measured, for example, under the following conditions.
[0078] Device name: SYSTEM-21Shodex (manufactured by Showa Denko Co., Ltd.)
[0079] Chromatographic column: connect 3 PL gel MIXED-B in series
[0080] Temperature: 40℃
[0081] Detection: Differential refractive index
[0082] Solvent: Tetrahydrofuran
[0083] Concentration: 2 mass%
[0084] Calibration curve: prepared using standard polystyrene (PS) (manufactured by PL Corporation).
[0085] <Number Average Molecular Weight of Copolymer (Mn)>
[0086] The number average molecular weight (Mn) of the copolymer of the present embodiment is preferably 10,000 to 40,000, more preferably 20,000 to 40,000. Specifically, for example, it is preferably 1, 2, 3, or 40,000, and may also be in the range between any two of the numerical values exemplified herein. If the number average molecular weight (Mn) of the copolymer is 10,000 or more, the amount of chain transfer agent used in the polymerization step of the copolymer is reduced, so that the amount of VOC contained in the obtained copolymer can be reduced. If it is 40,000 or less, the solubility of the copolymer in MEK or the curability of the thermosetting resin composition prepared with the copolymer can be improved.
[0087] To control the number average molecular weight (Mn) of the copolymer, in addition to adjusting the polymerization temperature, polymerization time, and the amount of polymerization initiator added, there are also methods such as adjusting the solvent concentration and the amount of chain transfer agent added.
[0088] The number average molecular weight (Mn) of the copolymer is a value measured by gel permeation chromatography (GPC) in terms of polystyrene, and can be measured, for example, under the same conditions as those for the weight average molecular weight (Mw).
[0089] <Number of unsaturated anhydride monomer units per molecular chain of copolymer>
[0090] The number of unsaturated anhydride monomer units in each molecular chain of the copolymer of the present embodiment is preferably 2 to 25, more preferably 3 to 16, and further preferably 4 to 12. Specifically, the number of unsaturated anhydride monomer units in each molecular chain of the copolymer is preferably, for example, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 15, 20, or 25, and may also be in the range between any two of the numerical values exemplified herein. If the number of unsaturated anhydride monomer units in each molecular chain of the copolymer is 2 or more, the curability of the thermosetting resin composition formulated with the copolymer is improved, and if it is 25 or less, the balance between the thermal decomposition of the copolymer and the curability of the thermosetting resin composition formulated with the copolymer is improved.
[0091] To control the number of unsaturated acid anhydride monomer units per molecular chain of the copolymer, there are methods such as adjusting the content of the unsaturated acid anhydride monomer units in the copolymer or the number average molecular weight (Mn) of the copolymer.
[0092] The number (N) of unsaturated acid anhydride monomer units in each molecular chain of the copolymer can be calculated by the following formula (1) from the content (A, unit: mass %) of the unsaturated acid anhydride monomer units in the copolymer when the total amount of the monomer units contained in the copolymer is set to 100 mass % and the number average molecular weight (Mn) of the copolymer.
[0093] N=(A / 100)×Mn / 98 Formula (1)
[0094] <Glass transition temperature Tg of copolymer>
[0095] The glass transition temperature (Tg) of the copolymer of the present embodiment is preferably 125°C to 200°C, more preferably 130°C to 190°C, and further preferably 135°C to 180°C. Specifically, for example, it is preferably 125, 130, 135, 140, 150, 155, 160, 165, 170, 175, 180, 185, 190, 195, or 200°C, and may also be in the range between any two of the numerical values exemplified herein. If the glass transition temperature (Tg) of the copolymer is 125°C or more, the heat resistance of the thermosetting resin composition formulated with the copolymer is improved, and if it is 200°C or less, the solubility of the copolymer in MEK can be improved.
[0096] The glass transition temperature (Tg) of the copolymer can be controlled by adjusting the content of the maleimide monomer unit contained in the copolymer or the weight average molecular weight of the copolymer, for example.
[0097] The glass transition temperature is an intermediate glass transition temperature (Tmg) measured by DSC (Differential scanning calorimetry) in accordance with JIS K-7121, and is a value measured under the measurement conditions described below.
[0098] Device name: Robot DSC6200 manufactured by Seiko Instruments Inc.
[0099] Heating rate: 10℃ / min
[0100] <Amount of Residual Aromatic Vinyl Monomer in Copolymer>
[0101] The amount of the residual aromatic vinyl monomer in the copolymer of the present embodiment is preferably 0 to 500 ppm, more preferably 0 to 400 ppm, and further preferably 0 to 300 ppm. Specifically, for example, it is preferably 1, 50, 100, 150, 200, 250, 300, 350, 400, 450, or 500 ppm or less. If the amount of the residual aromatic vinyl monomer in the copolymer is 500 ppm or less, the amount of VOC contained in the copolymer can be reduced.
[0102] Regarding the amount of residual aromatic vinyl monomers in the copolymer, as a pretreatment, 0.3-0.4 g of the copolymer was weighed in a 50 ml conical flask, and 10 ml of DMF (dimethylformamide) added with an internal standard (cyclopentanol) was added to dissolve it, and then the measurement was carried out under the following conditions.
[0103] Device name: GC-12A (manufactured by Shimadzu Corporation)
[0104] Detector: FID (Flame Ionization Detector)
[0105] Chromatographic column: 3m glass chromatographic column (filler: liquid phase PEG20M+TCEP(15+5))
[0106] Temperature: INJ 150℃, DET 150℃, Column 115℃
[0107] Injection volume: 1μL
[0108] The amount of the residual aromatic vinyl monomer in the copolymer can be reduced by, for example, reducing the amount of the chain transfer agent in the polymerization step.
[0109] <Amount of Residual Maleimide Monomer in Copolymer>
[0110] The amount of the residual maleimide monomer in the copolymer of the present embodiment is preferably 0 to 500 ppm, more preferably 0 to 400 ppm, and further preferably 0 to 300 ppm. Specifically, for example, it is preferably 1, 50, 100, 150, 200, 250, 300, 350, 400, 450, or 500 ppm or less. If the amount of the residual maleimide monomer in the copolymer is 500 ppm or less, the amount of VOC contained in the copolymer can be reduced.
[0111] The amount of the residual maleimide monomer in the copolymer is measured under the following conditions.
[0112] Device name: GC-2010 (manufactured by Shimadzu Corporation)
[0113] Chromatographic column: Capillary column DB-5MS (phenyl propadiene polymer)
[0114] Temperature: injection port 280℃, detector 280℃
[0115] The temperature analysis was performed at a column temperature of 80°C (initial).
[0116] (Temperature analysis conditions)
[0117] 80℃: Keep for 12 minutes
[0118] 80~280℃: Heat up at 20℃ / min for 10 minutes
[0119] 280℃: hold for 10 minutes
[0120] Detector: FID
[0121] Steps: Dissolve 0.5g of sample in 5ml of 1,2-dichloroethane solution (0.014g / L) with undecane (internal standard). Then, add 5ml of n-hexane and shake with an oscillator for 10 to 15 minutes to precipitate. In the state where the polymer is precipitated and precipitated, only the supernatant is injected into GC (gas chromatograph). Calculate the quantitative value based on the peak area of the obtained monomer and the coefficient obtained from the internal standard.
[0122] The amount of the residual maleimide monomer in the copolymer can be reduced by, for example, adopting a post-imidization method in the production of the copolymer.
[0123] <Characteristics of Copolymer>
[0124] <Thermal Stability of Copolymer>
[0125] The copolymer of the present embodiment has excellent thermal stability. Here, the thermal stability of the copolymer is an index evaluated based on the 5 mass % reduction temperature obtained by thermogravimetric analysis (TGA), which is a value measured at a temperature increase rate of 5° C. / min in a nitrogen atmosphere.
[0126] When the copolymer has a high 5 mass % reduction temperature obtained by thermogravimetric analysis (TGA) and has excellent thermal stability, the reactive curing agent containing the copolymer also has excellent thermal stability.
[0127] <Solubility of Copolymer in MEK>
[0128] The copolymer of this embodiment has excellent solubility in methyl ethyl ketone (MEK). Here, the solubility of the copolymer in MEK is defined by the weight percent concentration (wt%) of the MEK solution, in which the maximum amount of the copolymer that can be dissolved in 10 g of MEK at 23°C is dissolved.
[0129] Specifically, a specific amount of copolymer is added to MEK at 23°C in three times, and the copolymer is dissolved by stirring. At this time, the copolymer is added for the second time 1 hour after the first addition of the copolymer, and the copolymer is added for the third time 1 hour after the second addition of the copolymer. After the third addition of the copolymer, it is confirmed that all the copolymers added within 4 hours are completely dissolved. The amount of the specific amount of copolymer to be dissolved is changed, the maximum amount of the copolymer that can be dissolved is obtained, and the weight percentage concentration (wt%) of the MEK solution when the maximum amount of the copolymer is dissolved is calculated.
[0130] The copolymer of the present embodiment has excellent solubility in methyl ethyl ketone (MEK), therefore, the reactive curing agent obtained by allocating the copolymer also has excellent solubility in MEK. Therefore, the reactive curing agent of the present embodiment is used as a reactive curing agent of a thermosetting resin composition impregnated in glass fiber when manufacturing the prepreg of copper clad laminate (CCL), and the deployment amount of the copolymer in the thermosetting resin composition can be increased. If the deployment amount of the copolymer in the thermosetting resin composition becomes more, the characteristics of the various monomer units contained in the copolymer can be fully utilized to enhance the characteristics of the thermosetting resin composition, such as heat resistance, etc. Furthermore, when the solubility in MEK is excellent, it can be expected that the solubility in solvents other than MEK used in the manufacture of CCL, such as acetone, toluene, cyclohexanone, etc., is also excellent.
[0131] <Thermosetting resin composition prepared with a reactive curing agent>
[0132] The reactive curing agent of the present embodiment can be mixed with a thermosetting resin to obtain a thermosetting resin composition. As the thermosetting resin, for example, a resin impregnated in glass fiber in the manufacture of a prepreg of a copper clad laminate (CCL) can be used, for example, epoxy resin, cyanate resin, bismaleimide resin, etc.
[0133] The thermosetting resin composition may contain other resins, additives, etc. as necessary.
[0134] <Other resins>
[0135] In the thermosetting resin composition obtained by preparing the reactive curing agent of this embodiment, elastomers such as butadiene rubber, isoprene rubber, acrylic rubber, graft copolymers containing these, and hydrogenated products of the graft copolymers can be prepared within a range that does not impair the effects of the present invention to enhance the peel strength between the thermosetting resin composition and the metal foil.
[0136] <Additives>
[0137] In the thermosetting resin composition obtained by preparing the reactive curing agent of this embodiment, a curing agent such as styrene-maleic anhydride copolymer can be supplementally added to the reactive curing agent of the present invention and formulated to improve curability within a range that does not impair the effects of the present invention.
[0138] Furthermore, for the purpose of accelerating the curing property of the curing agent, an amine curing accelerator, an imidazole curing accelerator, a phosphorus curing accelerator, or the like may be blended within a range that does not impair the effects of the present invention.
[0139] Furthermore, for the purpose of imparting flame retardancy to the thermosetting resin composition, flame retardants such as phosphate-based flame retardants such as tricresyl phosphate and triphenyl phosphate, and inorganic substances such as red phosphorus, antimony trioxide, aluminum hydroxide, and magnesium hydroxide may be formulated within a range that does not impair the effects of the present invention.
[0140] In order to achieve a low thermal expansion coefficient and a high elastic modulus, an inorganic filler such as silica, mica, talc, short glass fibers, fine glass powder, and hollow glass may be blended within a range that does not impair the effects of the present invention.
[0141] <Manufacturing of Thermosetting Resin Composition>
[0142] The thermosetting resin composition is obtained by dissolving the reactive curing agent of the present embodiment, the thermosetting resin, and other resins or additives in an organic solvent and mixing them. Examples of such organic solvents include ketones such as MEK, cyclohexanone, and methyl isobutyl ketone.
[0143] <Characteristics of Thermosetting Resin Composition>
[0144] <Heat resistance of thermosetting resin composition>
[0145] The thermosetting resin composition obtained by mixing the reactive curing agent of the present embodiment has excellent heat resistance. Here, the heat resistance of the thermosetting resin composition is a property evaluated based on the glass transition temperature (Tg) measured by DSC according to JIS C 6481. Here, the glass transition temperature (Tg) is the middle glass transition temperature (Tmg), which is a measured value under the measurement conditions described below.
[0146] Device name: Robot DSC6200 manufactured by Seiko Instruments Inc.
[0147] Heating rate: 10℃ / min
[0148] The thermosetting resin composition obtained by preparing the reactive curing agent of the present embodiment uses a reactive curing agent with improved solubility in MEK, so the amount of the reactive curing agent that can be prepared in the thermosetting resin composition is increased. The reactive curing agent of the present embodiment contains a maleimide-based monomer unit that can help improve the heat resistance of the thermosetting resin composition, so the thermosetting resin composition has excellent heat resistance.
[0149] Furthermore, for example, when a styrene-maleic anhydride copolymer and the reactive curing agent of the present embodiment are used together as a curing agent for a thermosetting resin, a thermosetting resin composition obtained by blending the reactive curing agent of the present embodiment also has excellent heat resistance.
[0150] The thermosetting resin composition obtained by mixing the reactive curing agent of the present embodiment adopts a reactive curing agent with improved solubility in MEK, so the amount of reactive curing agent that can be mixed in the thermosetting resin composition becomes larger. Therefore, the mixing amount of the styrene-maleic anhydride copolymer used in the thermosetting resin composition can be reduced. The glass transition temperature of the styrene-maleic anhydride copolymer is lower than that of the reactive curing agent of the present embodiment, so the mixing amount of the styrene-maleic anhydride copolymer in the thermosetting resin composition can be reduced, and as a result, the heat resistance of the thermosetting resin composition is excellent.
[0151] <Curing Properties of Thermosetting Resin Composition>
[0152] The thermosetting resin composition obtained by blending the reactive curing agent of the present embodiment can also have excellent curability by adjusting the number average molecular weight of the copolymer.
[0153] The curability of a thermosetting resin composition is a property evaluated based on the degree of curing of the resin calculated from the glass transition temperature (Tg) measured by the TMA (thermomechanical analysis) method under the following measurement conditions in accordance with JIS C 6481.
[0154] Device name: Q400 manufactured by TAInstruments Japan Co., Ltd.
[0155] Heating rate: 5℃ / min
[0156] The thermosetting resin composition obtained by preparing the reactive curing agent of this embodiment uses a reactive curing agent with improved solubility in MEK, so the amount of reactive curing agent that can be prepared in the thermosetting resin composition is increased. The reactive curing agent of this embodiment contains an unsaturated acid anhydride monomer unit that can react with the thermosetting resin in the thermosetting resin composition, so it can improve the curability of the thermosetting resin composition.
[0157] <Moisture Absorption Resistance of Cured Product of Thermosetting Resin Composition>
[0158] The cured product of the thermosetting resin composition obtained by blending the reactive curing agent of the present embodiment can also have excellent moisture absorption resistance by reducing the amount of the unsaturated acid anhydride monomer unit in the copolymer.
[0159] The moisture absorption resistance of a cured product of a thermosetting resin composition is a property evaluated based on the water absorption rate measured in accordance with JIS C 6481.
[0160] In particular, when the styrene-maleic anhydride copolymer and the reactive curing agent of the present embodiment are used in combination, the thermosetting resin composition obtained by mixing the reactive curing agent of the present embodiment adopts a reactive curing agent with improved solubility in MEK, so the amount of the reactive curing agent that can be mixed in the thermosetting resin composition becomes more. Therefore, the mixing amount of the styrene-maleic anhydride copolymer used in combination in the thermosetting resin composition can be reduced. The hygroscopicity of the styrene-maleic anhydride copolymer is higher than that of the reactive curing agent of the present embodiment, so the mixing amount of the styrene-maleic anhydride copolymer in the thermosetting resin composition can be reduced, and as a result, the thermosetting resin composition has excellent hygroscopicity resistance.
[0161] [Example]
[0162] Hereinafter, the details will be described using examples, but the present invention is not limited to the following examples.
[0163] In the table, St represents styrene, AN represents acrylonitrile, NPMI represents N-phenylmaleimide, MAH represents maleic anhydride, and MEK represents methyl ethyl ketone.
[0164] <Example 1: Synthesis of Copolymer (P-1)>
[0165] In an autoclave with a capacity of about 120 liters equipped with a stirrer, 83 parts by mass of styrene, 1 part by mass of maleic anhydride, 0.6 parts by mass of α-methylstyrene dimer, and 26 parts by mass of methyl ethyl ketone were added, and after replacing the gas phase with nitrogen, the temperature was raised to 92°C over 40 minutes while stirring. After the temperature was raised, a solution of 16 parts by mass of maleic anhydride and 0.6 parts by mass of tert-butyl peroxy 2-ethylhexanoate dissolved in 78 parts by mass of methyl ethyl ketone was continuously added over 5 hours while maintaining 92°C. After the addition was completed, the temperature was raised to 120°C, and the reaction was allowed to proceed for 1 hour to terminate the polymerization. Thereafter, 15 parts by mass of aniline and 0.3 parts by mass of triethylamine were added to the polymerization solution, and the reaction was allowed to proceed at 140°C for 6 hours. The imidization reaction solution after the reaction was completed was put into a vented screw extruder, and the volatile matter was removed to obtain a granular copolymer. The obtained granules were crushed with a rotary blade mill to obtain a powdery copolymer (P-1). Through the following 13 The composition analysis of the copolymer (P-1) by C-NMR method revealed 74.0 mass % of styrene, 23.0 mass % of N-phenylmaleimide, and 3.0 mass % of maleic anhydride. The analysis results of the obtained copolymer (P-1) are shown in Table 1.
[0166] <Composition Analysis>
[0167] The composition of copolymer (P-1) was analyzed by 13 The C-NMR method was measured under the measurement conditions described below.
[0168] Device name: FT-NMR AVANCE300 (manufactured by BRUKER)
[0169] Solvent: deuterated chloroform
[0170] Concentration: 14% by mass
[0171] Temperature: 27℃
[0172] Cumulative times: 8000 times
[0173] <Weight average molecular weight (Mw) and number average molecular weight (Mn)>
[0174] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the copolymer (P-1) are polystyrene-equivalent values measured by gel permeation chromatography (GPC), and are measured under the following conditions.
[0175] Device name: SYSTEM-21Shodex (manufactured by Showa Denko Co., Ltd.)
[0176] Chromatographic column: connect 3 PL gel MIXED-B in series
[0177] Temperature: 40℃
[0178] Detection: Differential refractive index
[0179] Solvent: Tetrahydrofuran
[0180] Concentration: 2 mass%
[0181] Calibration curve: prepared using standard polystyrene (PS) (manufactured by PL Corporation).
[0182] <Number of unsaturated anhydride monomer units per molecular chain of copolymer>
[0183] The number (N) of unsaturated acid anhydride monomer units in each molecular chain of the copolymer (P-1) is calculated by the following formula (1) from the content (A, unit: mass %) of the unsaturated acid anhydride monomer units in the copolymer (P-1) when the total of the monomer units contained in the copolymer (P-1) is set to 100 mass % and the number average molecular weight (Mn) of the copolymer (P-1).
[0184] N=(A / 100)×Mn / 98 Formula (1)
[0185] <Glass transition temperature (Tg)>
[0186] The glass transition temperature of the copolymer (P-1) is the middle glass transition temperature (Tmg) measured by DSC in accordance with JIS K-7121, and is measured under the measurement conditions described below.
[0187] Device name: Robot DSC6200 manufactured by Seiko Instruments Inc.
[0188] Heating rate: 10℃ / min
[0189] <Solubility in MEK>
[0190] The solubility of copolymer (P-1) in MEK was evaluated based on the weight percent concentration (wt %) of the MEK solution in which the maximum amount of copolymer (P-1) that can be dissolved in 10 g of MEK at 23°C was dissolved.
[0191] At 23°C, a specific amount of copolymer (P-1) is added to 10 g of MEK in three portions, and the copolymer is dissolved by stirring. At this time, the copolymer (P-1) is added for the second time 1 hour after the first addition of the copolymer (P-1), and the copolymer (P-1) is added for the third time 1 hour after the second addition of the copolymer (P-1). After the third addition of the copolymer (P-1), confirm that all the copolymers (P-1) added within 4 hours are completely dissolved. The amount of the specific amount of copolymer (P-1) to be dissolved is changed to determine the maximum amount of the copolymer (P-1) that can be dissolved. Calculate the weight percentage concentration (wt%) of the MEK solution when the maximum amount of the copolymer (P-1) is dissolved.
[0192] <Amount of Residual Styrene Monomer>
[0193] The amount of residual styrene monomer in the copolymer (P-1) is measured by the following procedure.
[0194] As a pretreatment, 0.3 to 0.4 g of the copolymer (P-1) was weighed in a 50 ml conical flask, 10 ml of DMF to which an internal standard (cyclopentanol) was added was added to dissolve the copolymer (P-1), and measurement was performed under the following conditions.
[0195] Device name: GC-12A (manufactured by Shimadzu Corporation)
[0196] Detector: FID
[0197] Chromatographic column: 3m glass chromatographic column (filler: liquid phase PEG20M+TCEP(15+5))
[0198] Temperature: INJ 150℃, DET 150℃, Column 115℃
[0199] Injection volume: 1μL
[0200] <Amount of Remaining N-phenylmaleimide Monomer>
[0201] The amount of the residual N-phenylmaleimide monomer in the copolymer (P-1) was measured under the following conditions.
[0202] Device name: GC-2010 (manufactured by Shimadzu Corporation)
[0203] Chromatographic column: Capillary column DB-5MS (phenyl propadiene polymer)
[0204] Temperature: injection port 280℃, detector 280℃
[0205] The temperature analysis was performed at a column temperature of 80°C (initial).
[0206] (Temperature analysis conditions)
[0207] 80℃: Keep for 12 minutes
[0208] 80~280℃: Heat up at 20℃ / min for 10 minutes
[0209] 280℃: hold for 10 minutes
[0210] Detector: FID
[0211] Procedure: 0.5 g of copolymer (P-1) was dissolved in 5 ml of 1,2-dichloroethane solution (0.014 g / L) to which undecane (internal standard) was added. Then, 5 ml of n-hexane was added and the mixture was shaken with an oscillator for 10 to 15 minutes to precipitate the polymer. After the polymer was precipitated, only the supernatant was injected into the GC. The quantitative value was calculated based on the peak area of the obtained monomer and the coefficient obtained from the internal standard.
[0212] <Thermal Stability of Copolymer>
[0213] The 5 mass % reduction temperature of the copolymer (P-1) was measured by thermogravimetric analysis (TGA) at a temperature increase rate of 5° C. / min in a nitrogen atmosphere.
[0214] <Examples 2 to 24: Synthesis of copolymers (P-2) to (P-24)>
[0215] Copolymers (P-2) to (P-24) were obtained by the same operation as in the synthesis of copolymer (P-1) while appropriately adjusting the amount of monomers added, the amount of polymerization initiator, the amount of chain transfer agent, the amount of triethylamine, and the reaction time.
[0216] In addition, regarding the synthesis of the copolymer containing acrylonitrile monomer units, first, styrene, acrylonitrile, maleic anhydride, α-methylstyrene dimer, and methyl ethyl ketone were added to an autoclave.
[0217] In addition, regarding the copolymer (P-17), styrene, maleic anhydride, N-phenylmaleimide, α-methylstyrene dimer, and methyl ethyl ketone are first added to an autoclave. After the polymerization is completed, the imidization reaction is not carried out, and the polymerization reaction liquid is put into a venting screw extruder to remove volatiles to obtain a granular copolymer. The obtained particles are crushed with a rotary blade type pulverizer to obtain a powdered copolymer (P-17).
[0218] For copolymers with relatively low molecular weight, the imidization reaction liquid after the reaction is completed is put into a venting screw extruder, and after removing the volatile matter, the copolymer is recovered without going through a pelletization step. The recovered copolymer is pulverized with a rotary blade pulverizer to obtain a powdered copolymer.
[0219] The compositions and properties of copolymers (P-2) to (P-24) were measured by the same methods as those for copolymer (P-1).
[0220] The compositions and properties of copolymers (P-2) to (P-24) are shown in Tables 1 and 2.
[0221] <Comparative Examples 1 to 9: Synthesis of Copolymers (PB-1) to (PB-9)>
[0222] Copolymers (PB-1) to (PB-9) were obtained by the same operation as in the synthesis of copolymer (P-1) while appropriately adjusting the amount of monomers added, the amount of polymerization initiator, the amount of chain transfer agent, the amount of triethylamine, and the reaction time.
[0223] For copolymers with relatively low molecular weight, the imidization reaction liquid after the reaction is completed is put into a venting screw extruder, and after removing the volatile matter, the copolymer is recovered without going through a pelletization step. The recovered copolymer is pulverized with a rotary blade pulverizer to obtain a powdered copolymer.
[0224] The compositions and physical properties of copolymers (PB-1) to (PB-9) were measured by the same methods as those for copolymer (P-1).
[0225] Table 3 shows the compositions and physical properties of copolymers (PB-1) to (PB-9).
[0226] <Production of epoxy resin compositions (R-1) to (R-24) and (RB-1) to (RB-9)>
[0227] Each copolymer (P-1) to (P-24), (PB-1) to (PB-9) as a reactive curing agent, 20 g of an epoxy resin (trade name: EPICLON N-673, manufactured by DIC Corporation), a styrene-maleic anhydride copolymer (the number of maleic anhydride monomer units in each molecular chain: 9, glass transition temperature: 120°C, trade name: EF40, manufactured by Polyscope Corporation) as a combined curing agent, and 15 g of a flame retardant (PX-200, Daitu Chemical Industry Co., Ltd.) were dissolved in 40 g of MEK to obtain epoxy resin compositions (R-1) to (R-24), (RB-1) to (RB-9).
[0228] Furthermore, the blending amount of the copolymer as a reactive curing agent and the styrene-maleic anhydride copolymer as a curing agent used in combination were adjusted so that the total amount of the two curing agents was 10 g. Specifically, the blending amount Y (in g) of the copolymer and the blending amount Z (in g) of the styrene-maleic anhydride copolymer were adjusted as follows based on the value of the weight percentage concentration X (wt%) of the MEK solution when the maximum amount of the copolymer was dissolved measured in the evaluation of the solubility of the copolymer in MEK.
[0229] When X (wt%) is 0 wt% or more and less than 50 wt%,
[0230] The amount of copolymer Y = 2 × X × (10 / 100),
[0231] The blending amount of the styrene-maleic anhydride copolymer is Z=10-Y.
[0232] When X (wt%) is 50wt% or more,
[0233] The amount of copolymer Y = 10,
[0234] The blending amount of the styrene-maleic anhydride copolymer is Z=0.
[0235] <Characteristics of Epoxy Resin Composition>
[0236] <Heat resistance of epoxy resin composition after curing>
[0237] The heat resistance of the epoxy resin composition after curing was evaluated by the following method.
[0238] Sample preparation method: The epoxy resin composition was spread on a Kapton film, heated and dried at 160°C for 10 minutes, and the solid content was taken out by casting. Then, the solid content was used to press the film at a pressure of 25 kg / cm 2 , and pressurizing was performed at a temperature of 185° C. for 90 minutes to obtain a resin plate.
[0239] ·Measuring method of heat resistance: The glass transition temperature (Tg) was measured by DSC in accordance with JIS C 6481. Here, the glass transition temperature (Tg) is the middle glass transition temperature (Tmg), and is a value measured under the measuring conditions described below.
[0240] Device name: Robot DSC6200 manufactured by Seiko Instruments Inc.
[0241] Heating rate: 10℃ / min
[0242] Evaluation benchmark
[0243] A (very good): more than 180℃
[0244] B (excellent): more than 175°C and less than 180°C
[0245] C (good): more than 170°C and less than 175°C
[0246] D (slightly worse): 160°C or higher and 170°C or lower
[0247] E(poor): below 160℃
[0248] Tables 1 to 3 show the heat resistance of the epoxy resin compositions (R-1) to (R-24) and (RB-1) to (RB-9).
[0249] <Curing Properties of Epoxy Resin Composition>
[0250] The curability of the epoxy resin composition was evaluated by the following method.
[0251] Sample preparation method: The epoxy resin composition was spread on a Kapton film, heated and dried at 160°C for 10 minutes, and the solid content was taken out by casting method, which was used as the sample before curing. Then, the solid content was used to press the film at a pressure of 25 kg / cm 2 , pressurizing was performed at a temperature of 185°C for 90 minutes to obtain a cured sample.
[0252] ·Measuring method of curability: According to JIS C 6481, the glass transition temperature (Tg) was measured by TMA method and the degree of curing of the resin was calculated.
[0253] Device name: Q400 manufactured by TAInstruments Japan Co., Ltd.
[0254] Heating rate: 5℃ / min
[0255] Evaluation benchmark
[0256] A (very good): degree of curing exceeds 50
[0257] B (excellent): The degree of curing is more than 40 and less than 50
[0258] C (good): The degree of curing is more than 30 and less than 40
[0259] D (slightly poor): Curing degree is 20 or more but less than 30
[0260] E (poor): curing degree less than 20
[0261] Tables 1 to 3 show the curability of the epoxy resin compositions (R-1) to (R-24) and (RB-1) to (RB-9).
[0262] <Moisture Absorption Resistance of Cured Epoxy Resin Composition>
[0263] The moisture absorption resistance of the cured product of the epoxy resin composition was evaluated by the following method.
[0264] Sample preparation method: The epoxy resin composition was spread on a Kapton film, dried by heating at 160°C for 10 minutes, and the solid content was taken out by casting. Then, the solid content was used to form a film at a pressure of 25 kg / cm 2 , and pressurizing was performed at a temperature of 185° C. for 90 minutes to obtain a resin plate.
[0265] ·Measurement method: According to JIS C 6481, measure the water absorption
[0266] Evaluation benchmark
[0267] A (very good): less than 0.5%
[0268] B (excellent): 0.5% or more and less than 1.0%
[0269] C (good): 1.0% or more and less than 1.5%
[0270] D (slightly poor): 1.5 or more but less than 2.0%
[0271] E (poor): more than 2.0%
[0272] Tables 1 to 3 show the moisture absorption resistance of the cured products of the epoxy resin compositions (R-1) to (R-24) and (RB-1) to (RB-9).
[0273] [Table 1]
[0274]
[0275] [Table 2]
[0276]
[0277] [Table 3]
[0278]
[0279] In the epoxy resin composition prepared with the reactive curing agent of the embodiment, since the copolymer with improved solubility in MEK is used as the reactive curing agent, more copolymer can be prepared in the epoxy resin composition. Therefore, the heat resistance of the epoxy resin composition is improved due to the maleimide monomer unit contained in the copolymer.
[0280] In addition, when the styrene-maleic anhydride copolymer and the reactive curing agent of the present embodiment are used together as a curing agent for a thermosetting resin, the heat resistance of the epoxy resin composition obtained by blending the reactive curing agent of the example is also improved.
[0281] In the epoxy resin composition in which the reactive curing agent having the number average molecular weight of the copolymer appropriately adjusted is added, the curability of the epoxy resin composition is improved.
[0282] Furthermore, in an epoxy resin composition in which a reactive curing agent having a composition of monomer units contained in a copolymer is appropriately adjusted, by adding more copolymer to the epoxy resin composition, the amount of styrene-maleic anhydride copolymer, which is another curing agent used in combination, can be reduced, thereby improving the moisture absorption resistance of the cured product of the epoxy resin composition.
[0283] The reactive curing agent of the comparative example has poor performance in at least one of the following aspects: solubility in MEK and improvement in heat resistance of the epoxy resin composition when formulated in the epoxy resin composition.
[0284] Industrial Applicability
[0285] According to the present invention, a reactive curing agent having improved solubility in methyl ethyl ketone (MEK) and capable of improving the heat resistance of a thermosetting resin composition is provided. By blending the reactive curing agent in a thermosetting resin, the composition can be suitably used for applications requiring heat resistance.
[0286] Furthermore, the copolymer contained in the reactive curing agent of the present invention is also suitable for use as a heat resistance imparting agent for imparting heat resistance to ABS (acrylonitrile-butadiene-styrene) or other resins, or as a compatibilizing agent for polymer alloys.
Claims
1. A reactive curing agent, It comprises a copolymer containing an aromatic vinyl monomer unit, an unsaturated acid anhydride monomer unit, and a maleimide monomer unit, and The weight average molecular weight of the copolymer is greater than 10,000 and less than 90,000, The copolymer contains 3.0% by mass or more and less than 49.0% by mass of the maleimide-based monomer unit, when the total of the monomer units contained in the copolymer is 100% by mass.
2. The reactive curing agent according to claim 1, wherein When the total amount of the monomer units contained in the copolymer is 100% by mass, the copolymer contains 3.0 to 30.0% by mass of the maleimide-based monomer units.
3. The reactive curing agent according to claim 2, wherein When the total amount of the monomer units contained in the copolymer is 100% by mass, the copolymer includes: 45.0 to 96.9% by mass of the aromatic vinyl monomer units, 0.1 to 25% by mass of the unsaturated acid anhydride monomer unit, and 0.0 to 20.0% by mass of other monomer units.
4. The reactive curing agent according to any one of claims 1 to 3, wherein The number of the unsaturated anhydride monomer units contained in each molecular chain of the copolymer is 2 to 25.
5. The reactive curing agent according to any one of claims 1 to 3, wherein The glass transition temperature of the copolymer is 125-200°C.
6. The reactive curing agent according to any one of claims 1 to 3, wherein The weight average molecular weight of the copolymer is 15,000 to 80,000.
7. The reactive curing agent according to any one of claims 1 to 3, wherein The weight average molecular weight of the copolymer is 20,000 to 70,000.
Citation Information
Patent Citations
JP1973007434U